2017
DOI: 10.1037/xhp0000430
|View full text |Cite
|
Sign up to set email alerts
|

Distractor probability changes the shape of the attentional template.

Abstract: Theories of attention commonly refer to the "attentional template" as the collection of features in working memory that represent the target of visual search. Many models of attention assume that the template contains a veridical representation of target features, but recent studies have shown that the target representation is "shifted" away from distractor features in order to optimize their distinctiveness and facilitate visual search. Here, we manipulated the probability of target-similar distractors during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
110
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(120 citation statements)
references
References 84 publications
10
110
0
Order By: Relevance
“…In this context, no such special tuning occurred in anticipation of more heterogeneous distractors. On the other hand, experience with irrelevant information does seem to be necessary for improving the allocation of attention away from distractors within a given search array (Cunningham & Egeth, 2016;Geng et al, 2017;Vatterott & Vecera, 2012). Taken together, these results suggest that more precise distractor rejection requires repeated exposure to relevant and irrelevant visual features, implying that this improved tuning of attention could involve perceptual learning instead of, or in addition to, better cognitive control.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…In this context, no such special tuning occurred in anticipation of more heterogeneous distractors. On the other hand, experience with irrelevant information does seem to be necessary for improving the allocation of attention away from distractors within a given search array (Cunningham & Egeth, 2016;Geng et al, 2017;Vatterott & Vecera, 2012). Taken together, these results suggest that more precise distractor rejection requires repeated exposure to relevant and irrelevant visual features, implying that this improved tuning of attention could involve perceptual learning instead of, or in addition to, better cognitive control.…”
Section: Discussionmentioning
confidence: 86%
“…Recent research by Geng, DiQuattro, and Helm (2017) has directly shown that templates are indeed sharpened when distractors are more likely to be similar to the target, lending some support to the hypothesis that the template memory benefit is related to segregation of the target from concurrent distractors. One potentially important factor, t h o u g h , i s t h e c o n s i s t e n c y o f t a r g e t c o l o r s .…”
Section: Introductionmentioning
confidence: 86%
“…Although challenged by some, this dissociation indicates that distractors, even when similar to the target, can be more efficiently ignored when the search allows for goal‐directed feature selection. Intriguingly, recent evidence indicates that the (neural) representation of the target template in working memory does not necessarily need to be a veridical copy of the target, but is a highly dynamic representation that can be flexibly adapted to also incorporate distractor information . That is, the target template representation can be strategically shifted off‐veridical to optimize the ability to distinguish targets from distractors and thereby improve attentional selectivity .…”
Section: Indirect Preparatory Distractor Suppressionmentioning
confidence: 99%
“…Intriguingly, recent evidence indicates that the (neural) representation of the target template in working memory does not necessarily need to be a veridical copy of the target, but is a highly dynamic representation that can be flexibly adapted to also incorporate distractor information. 26,[60][61][62] That is, the target template representation can be strategically shifted off-veridical to optimize the ability to distinguish targets from distractors and thereby improve attentional selectivity. 17 Fine-tuning of the target template in relation to distractor features may take place in the lateral prefrontal cortex due to the abundance of neurons with mixed selectivity in this area.…”
Section: Indirect Distractor Suppression Through Template-to-distractmentioning
confidence: 99%
“…In general, search performance is best when people know in advance the exact features that define the distractors and the targets (Schoonveld, Shimozaki, & Eckstein, 2007;Eckstein, 2011). In fact, in some situations it has even been shown that participants often base their target template not on the optimal way of detecting the target but on the optimal way of distinguishing the target from the distractors (e.g., Navalpakkam and Itti, 2007;Scolari & Serences, 2009;Geng, DiQuattro & Helm, 2017;Yu & Geng, 2019).…”
Section: The Role Of Distractors In Searchmentioning
confidence: 99%